Efeito de extratos metanólicos de stryphnodendron adstringens (MART) coville na alimentação e reprodução de Plutella xylostella L. (Lepidoptera: Plutellidae) - Fonseca, Jussara; Couto, Irys Fernanda Santana; Da Silva Matias, Rosicléia; Fioratti, Claudemir Antonio Garcia; Pereira, Fabricio Fagundes; Mauad, Munir [UNESP]; De Paula Quintão Scalon, Silvana; Carvalho, Emerson Machado [UNESP]; Mussury, Rosilda Mara [UNESP] (My University, 2018)
Expecting to find plants with insecticidal potential in the Cerrado biodiversity we searched numerous plant species and, among them Stryphnodendron adstringens ( Mart) C oville, a plant locally known as 'barbatimão' that has been used for several purposes in the State of Mato Grosso do Sul, Brazil. The objective was to determine the feeding and oviposition preference of Plutella xylostella L . f or m ethanolic e xtracts o f barbatimão leaves and bark, during the immature phase of insect development. The feeding preference of larvae, oviposition and egg viability were evaluated at extract concentrations of 0.5, 1.0 and 1.5mġml-1, and the phytochemical screening of the extract was performed. The feeding preference of P. xylostella f or c abbage l eaves t reated w ith t he m ethanolic e xtract (made of leaf and bark of S. adstringens) in concentration of 1.5mġml-1 was weak. As for the oviposition preference of the insect, all the extracts were antioxenotic but the use of methanolic extracts at concentrations of 1.0 and 1.5mġml-1 resulted in fewer eggs and hatched larvae. Phytochemical screening showed the presence of tannins, saponins, steroids, terpenes, alkaloids and flavonoids in the extracts of both leaves and bark. The antioxenotic effect is attributed to these compounds, with emphasis in tannins.
Effect of methanol extracts of Stryphnodendron adstringens (MART) coville on feeding and breeding of plutella xylostella L. (Lepidoptera: Plutellidae)